Physical rehabilitation after hip joint dislocation in the elderly - Monika Prylińska; Małgorzata Gajos; Jakub Husejko; Natalia Skierkowska; Beniamin Szmelcer; Aleksandra Modlińska; Karolina Cięszka; Marta Lipka; Weronika Topka; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Introduction: Hip joint injuries often have complex and multifactorial causes. Therefore it is so important to apply a properly adjusted physical therapy to each patient. It is especially important in case of older people, where in addition to regular force based trauma, there may exist a number of degenerative changes to the hip joint associated with the aging of the body. Aim The aim of this article is to review the available hip joint injury physical rehabilitation methods, including the newest physical rehabilitation trends. An assesment of the effectiveness of the discussed rehabilitation methods is also carried out in this paper. Material and methods: Articles in the EBSCO database have been analysed using keywords: injuries of the hip joints, dislocation of the hip joint, modern methods of rehabilitation, older people. Results: The most common type of hip injuries in elderly patients are proximal femur fracture, trochanteric fracture and femoral neck fracture. In case of such fractures the main choice is usually surgical treatment, therefore it is important to start the rehabilitation process as soon as possible to allow for a quick recovery of the joint. Anticoagulant therapy is introduced within the first 24 hours after the surgery. Verticalization and learning to walk is introduced in the following days, where it is crucial to strengthen the muscles. In later stages exercises with partial and full weighing of the limb can be introduced. Physical exercise therapy is proven to be effective in returning the geriatric patient to full mobility or improving his locomotor functions. Physiotherapy, i.e. hydrotherapy, balneotherapy, magnetotherapy, thermotherapy and laser therapy, can also be introduced for faster tissue regeneration and pain relief. An important element of the post-operative stage is educating the patient about post-hospital life, i.e. principles of safe behavior at home, his limitations and the gradual introduction of physical activity. Conclusions: The hip joint through its location, structure and function is one of the most common locations of degenerative changes and injuries in the overall population. It is particularly important in elderly people, due to degenerative changes associated with the aging of the body. Rehabilitation after hip injuries should be started as soon as possible after its occurrence. It is important to remember that geriatric patients are specific, due to various limitations, i.e. multimorbidity, polipharmacotherapy, frailty, deafness, amblyopia, sarcopenia and others. Therefore it is necessary to personalise rehabilitation process to best fit to each patient.